The Protective Effect of Ginger Extract Against Bisphenol A-induced Testicular Toxicity in NMRI Mice - SMA Shariatzadeh; A Hasanvand; H Fallah Huseini (Journal of Medicinal Plants, 2016)
Background: Bisphenol A (BPA) is a xenobiotic estrogenic compound and can also cause oxidative stress in testis tissue.